Adolescent Trauma During the COVID Pandemic: Just Like Adults, Children, or Someone Else?. Issue 10 (October 2022) - Ruhi-Williams, Perisa; Yeates, Eric O.; Grigorian, Areg; Schellenberg, Morgan; Owattanapanich, Natthida; Barmparas, Galinos; Margulies, Daniel; Juillard, Catherine; Garber, Kent; Cryer, Henry; Tillou, Areti; Burruss, Sigrid; et al.
COVID-19 stay-at-home (SAH) orders were impactful on adolescence, when social interactions affect development. This has the potential to change adolescent trauma. A post-hoc multicenter retrospective analysis of adolescent (13-17 years-old) trauma patients (ATPs) at 11 trauma centers was performed. Patients were divided into 3 groups based on injury date: historical control (CONTROL:3/19/2019-6/30/2019, before SAH (PRE:1/1/2020-3/18/2020), and after SAH (POST:3/19/2020-6/30/2020). The POST group was compared to both PRE and CONTROL groups in separate analyses. 726 ATPs were identified across the 3 time periods. POST had a similar penetrating trauma rate compared to both PRE (15.8% vs 13.8%, P = .56) and CONTROL (15.8% vs 14.5%, P = .69). POST also had a similar rate of suicide attempts compared to both PRE (1.2% vs 1.5%, P = .83) and CONTROL (1.2% vs 2.1%, P = .43). However, POST had a higher rate of drug positivity compared to CONTROL (28.6% vs 20.6%, P = .032), but was similar in all other comparisons of alcohol and drugs to PRE and POST periods (all P > .05). Hence ATPs were affected differently than adults and children, as they had a similar rate of penetrating trauma, suicide attempts, and alcohol positivity after SAH orders. However, they had increased drug positivity compared to the CONTROL, but not PRE group.